Plasmonic linewidth narrowing by encapsulation in a dispersive absorbing material - Ryan Peck; Ali Khademi; Juanjuan Ren; Stephen Hughes; Alexandre G. Brolo; Reuven Gordon (Physical Review Research, 2021)
It is often assumed that adding losses to a resonant system necessarily broadens the width of the resonance. Here, the scattering spectrum of gold nanoparticles in P3HT (strongly absorbing) and PMMA (low loss) were measured using dark field microscopy and surprisingly, the linewidth was halved in the lossy medium. To gain physical insight into this unusual result, a Green function analysis was employed, and the roles of the permittivity, both magnitude and dispersion, in reducing the linewidth when material losses are increased were made clear. This surprising route to narrower linewidths is intriguing for nanoplasmonic applications including sensing, spectroscopy, imaging and nanolasing and also more generally for resonant systems where loss is conventionally avoided.